The neuronal Golgi in neural circuit formation and reorganization - Nakagawa, Naoki (Frontiers in Neural Circuits, 2024)
The Golgi apparatus is a central hub in the intracellular secretory pathway. By positioning in the specific intracellular region and transporting materials to spatially restricted compartments, the Golgi apparatus contributes to the cell polarity establishment and morphological specification in diverse cell types. In neurons, the Golgi apparatus mediates several essential steps of initial neural circuit formation during early brain development, such as axon-dendrite polarization, neuronal migration, primary dendrite specification, and dendritic arbor elaboration. Moreover, neuronal activity-dependent remodeling of the Golgi structure enables morphological changes in neurons, which provides the cellular basis of circuit reorganization during postnatal critical period. In this review, I summarize recent findings illustrating the unique Golgi positioning and its developmental dynamics in various types of neurons. I also discuss the upstream regulators for the Golgi positioning in neurons, and functional roles of the Golgi in neural circuit formation and reorganization. Elucidating how Golgi apparatus sculpts neuronal connectivity would deepen our understanding of the 2 cellular/molecular basis of neural circuit development and plasticity.